Transmissão post mortem de patrimônio digital: em defesa da ampla sucessão - Laura Marques Gonçalves (2021)
This paper aims at analyzing the destination of digital assets after the user's death, with focus on the patrimonial heritage and the legal framework which would apply to this data. The digital age brings its own particularities and difficulties that instigates the debate, as a matter of international relevance. There is a change of perspective in the immaterial era, with the inclusion of new elements in the heritage, which requires an approach to the understanding and classification of digital assets. The study thus discusses the perspectives of digital inheritance and investigates the best theory on the transferability of digital assets. Based on the leading case judged by the Bundesgerichtshof, in Germany, the possibility of a broad succession of digital assets is investigated. The paper intends to analyze developments of heritage in digital assets, considering the opposing interests among the providers’ provisions, heirs’ rights and users’ autonomy, investigating the possibility of postmortem patrimonial exploitation in the light of Brazilian judicial scenario and relevant international experiences on the subject. Lastly, the paper presents a critical chart of draft legislation in progress in the Brazilian Congress, offering possible solutions to the challenges surrounding it.